Issues of language and literacy revisited - Youssef, Valerie; Drayton, Kathy-Ann (School of Education, UWI, St. Augustine, 2008)
This paper reviews the present state of academic and medical knowledge on the problems that children encounter in acquiring both language and literacy, and concludes that we need to face the issues on other fronts than those we are engaging at the present. On the one hand, there are issues of acquiring literacy in the vernacular before transferring those skills to the Standard as the second variety. On the other, there is a source of the problems that we have not begun to engage-the need for full Speech-Language screening of children on school entry so that conditions which are likely to result in potential deficits in both language and literacy can be identified and intervention measures implemented to ensure that these deficits are largely overcome. Now that we are training persons who can support our few Speech-Language pathologists in the screening, process, it is time for us to take on board seriously the 12-20 percent of children we are losing every year through failure that is not of our making
Keywords: Primary school students; Language policy; Educational policies; Literacy; Child language; Language development; Language proficiency; Trinidad and Tobago